1999
DOI: 10.1021/om9902535
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Electron-Deficient Benzoheterocycle Triosmium Clusters. 5. The Chemistry of Os3(CO)932-(C(9)−N)-5,6-benzoquinolyl)(μ-H) and Its Phosphine Derivative

Abstract: The reactivity of Os3(CO)9(μ3-η2-C13H8N)(μ-H) (1) is reported. The reaction of 1 with triphenyl phosphine gives Os3(CO)9(μ-η2-C13H8N)(μ-H)(PPh3) (2), in which the phosphine is bonded to the same osmium as the C(10) of the heterocyclic ring, isostructural with the quinoline analogue. Thermal or photochemical decarbonylation of 2 gives moderate yields of Os3(CO)8(μ3-η3-C13H8N)(μ-H)PPh3 (3), which has a σ−π-vinyl bonding mode with the C(9)−C(10) double bond and not the expected μ3-η2 electron-deficient bonding mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…In summary, the room temperature reaction between electron-deficient 1 and PPh3 affords the (R = H, Me) [27], but is quite different from those observed for its quinolinate [3,5] and 5,6benzoquinolinate analogs [8]. This study also confirms that a small change in the benzoheterocycle significantly affects the reactivity of the resultant phosphine adducts of these electron-deficient clusters towards phosphines.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In summary, the room temperature reaction between electron-deficient 1 and PPh3 affords the (R = H, Me) [27], but is quite different from those observed for its quinolinate [3,5] and 5,6benzoquinolinate analogs [8]. This study also confirms that a small change in the benzoheterocycle significantly affects the reactivity of the resultant phosphine adducts of these electron-deficient clusters towards phosphines.…”
Section: Discussionmentioning
confidence: 53%
“…Studies also showed that the nature of the heterocyclic ligands somehow influences the reactivity of the resultant phosphine adducts. For example, photolysis or thermolysis of these phosphine adducts usually leads to nonspecific decomposition or phosphine ligand dissociation to give the phosphine-free nona-and deca-carbonyl clusters [Os3(CO)9(μ3-η 1 ,κ 1 -L)(μ-H)] and [Os3(CO)10(μ-η 1 ,κ 1 -L)(μ-H)] [3,8]. However, an electron-precise σ-π vinyl complex was formed via carbonyl dissociation upon photolysis or thermolysis in the case of metallated 5,6benzoquinolate cluster as shown in Scheme 1 [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the reactions of the electron-deficient benzoheterocyclic triosmium clusters of the type [Os 3 (CO) 9 (l-H)(l 3 -g 2 -L-H)] (L = quinoline, quinoxaline, benzimidazole, benzothiazole, benzoxazole) obtained from decarbonylation of the corresponding decacabonyls [Os 3 (CO) 10 (l-H)(l-g 2 -L-H)], with neutral nucleophiles such as phosphine and amines results in ligand addition at the metal core along with rearrangements whereas reactions with anionic nucleophiles such as hydride or carbanions results in attack at the carbocyclic ring [4][5][6][17][18][19][20]23] (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed synthetic procedures for a class of benzoheterocycle triosmium clusters of general formula [(l-H)Os 3 (CO) 9 (L)(l 3 -g 2 -(Q-H))], where L = [P(C 6 H 4 SO 3 Na) 3 ] or [P(OCH 2 CH 2 NMe 3 I) 3 ] and Q = quinoline, 3-aminoquinoline, quinoxaline, phenanthridine [23][24][25][26][27][28][29][30] (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%